CULTURE-BASED MICROBIOLOGICAL ASSESSMENT OF BACTERIAL COMMUNITY IN SOILS FROM WASTE DUMPSITES WITHIN GOMBE METROPOLIS, NIGERIA - H.I, IBRAHIM.; ABDULRASHEED M; ABDULRASHEED. M; IBRAHIM. S (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Waste dumpsites or landfills is an area of land where refuse or waste materials from differed processes, activities and sources are deposited. This study was aimed at applying a culturebased approach for assessing the culturable bacterial community in soils from waste dumpsites within Gombe metropolis for environmental relevance. Exactly thirty (30) soil samples were collected from 10 different dumpsites and were examined bacteriologically by serial dilution then pour plating on several culture media. Afterwards, bacteria isolated after 24 h incubation were macroscopically, microscopically and biochemically examined for genuine identification and confirmation. Also, the bacterial plate counts of the respective dumpsites were determined. The bacterial load from the mean plate count were 3.33x109, 3.1x109, 1.43x109, 2.77x109, 2.13x109, 3.20x109, 4.20x109, 3.23x109, 2.03x109 and 1.33x109 for Arawa, Bolari, Bagadaza, Hammadu Kafi, Cecenia, Riyal, Pantami, Malam Inna, State low-cost and Kagarawal respectively. Nine (9) bacteria genera/species isolated and identified were Staphylococcus aureus, Klebsiella pneumonia, Escherichia coli, Proteus mirabilis, Bacillus cereus, Salmonella sp, Enterobacter sp, Micrococcus sp and Shigella sp though with varied percentage of the occurrence. Findings from this study understandably portray low diversity of the bacterial population as only culturable bacterial community was reflected in commensuration with the approach applied. The detection of Staphylococcus aureus, Salmonella and Shigella in the refuse dumpsites soils confirmed microbial pathogen presence and depict an environmental and public health significance thus government and municipalities should provide annexe laws or revise existing policies regarding the locations, operation and management of dumpsites to safeguard the health and safety of the populace.